Endophytic Cultivable Bacteria of the Metal Bioaccumulator Spartina maritima Improve Plant Growth but Not Metal Uptake in Polluted Marshes Soils - Mesa, Jennifer; Mateos-Naranjo, Enrique; Caviedes, Miguel A.; Redondo-Gómez, Susana; Pajuelo, Eloisa; Rodríguez-Llorente, Ignacio D. (Frontiers in Microbiology, 2015)
Endophytic bacterial population was isolated from Spartina maritima tissues, a heavy metal bioaccumulator cordgrass growing in the estuaries of Tinto, Odiel and Piedras River (south west Spain), one of the most polluted areas in the world. Strains were identified and ability to tolerate salt and heavy metals along with plant growth promoting and enzymatic properties were analysed. A high proportion of these bacteria were resistant towards one or several heavy metals and metalloids including As, Cu and Zn, the most abundant in plant tissues and soil. These strains also exhibited multiple enzymatic properties as amylase, cellulase, chitinase, protease and lipase, as well as plant growth promoting properties, including nitrogen fixation, phosphates solubilisation and production of indole-3-acetic acid (IAA), siderophores and 1-aminocyclopropane-1-carboxylate (ACC) deaminase. The best performing strains (Micrococcus yunnanensis SMJ12, Vibrio sagamiensis SMJ18 and Salinicola peritrichatus SMJ30) were selected and tested as a consortium by inoculating S. maritima wild plantlets in greenhouse conditions along with wild polluted soil. After 30 days, bacterial inoculation improved plant photosynthetic traits and favoured intrinsic water use efficiency. However, far from stimulating plant metal uptake, endophytic inoculation lessened metal accumulation in above and belowground tissues. These results suggest that inoculation of S. maritima with indigenous metal-resistant endophytes could mean a useful approach in order to accelerate both adaption and growth of this indigenous cordgrass in polluted estuaries in restorative operations, but may not be suitable for rhizoaccumulation purposes.